Generation of sub-daily precipitation time series anywhere in Switzerland by mapping the parameters of GWEX-MRC, an at-site weather generator - Kaltrina Maloku; Guillaume Evin; Benoit Hingray (Journal of Hydrology: Regional Studies)
Study RegionSwitzerlandStudy FocusStochastic weather generators (WGENs) are a common tool for generating long precipitation scenarios, also needed at ungauged sites. This study evaluates different methods for obtaining the parameters of a hybrid at-site WGEN at any location within the study area. The hybrid GWEX-MRC model is composed of GWEX, a daily WGEN, and MRC, a disaggregation model based on multiplicative random cascades. Two approaches are considered for obtaining parameter maps. The first approach applies classical spatial interpolation techniques, kriging and thin-plate splines, to parameter estimates derived from rain gauge data. The second approach uses CombiPrecip, an hourly gridded precipitation product from MeteoSwiss, to estimate parameters at grid scale. New Hydrological Insights for the RegionWe find that the parameters of GWEX-MRC can be interpolated with satisfactory results across Switzerland. Among interpolation techniques, kriging with elevation as an external drift performs best for GWEX, while thin-plate spline with elevation gives better results for MRC. The comparison of the two approaches, interpolation of site-based estimates and direct parameter estimation using CombiPrecip, showed comparable or slightly different performance depending on the precipitation statistic and season. These findings reveal the feasibility of both approaches and provide insights into their relative strengths and limitations. In addition, this study demonstrates that long precipitation scenarios can be reliably generated throughout Switzerland, which can later be used to feed a hydrological model.